The farmers' perception toward Paddy Purchasing Centre (PPC) by Farmers Organizations Authority (FOA) in Machang, Kelantan - Sulaiman, Ahmad Mushaimi (2015)
Paddy was the third planted crop that is widely grown in Malaysia after oil palm and rubber. It was a staple food in the country so, a lot effort need to be done in ensuring the production of rice keep increased. Although we were also producing rice, it was still not enough to fill the demand due to increasing population in the country. There were a lot of granary areas in Malaysia such as in Kelantan, Kedah, Terengganu, Perlis, Selangor, Sabah, Sarawak and others. In Malaysia, the rice was processing in Malaysia at the factories that are owned mostly by Padi Beras Nasional (BERNAS). BERNAS was the large company that were responsible for the paddy industry in Malaysia. Usually, farmers would sell their yield to the manufactures through the middle man especially in inland areas. However, there was an initiative made by Pertubuhan Peladang Kawasan (PPK) to establish Paddy Purchasing Centre (PPC) to avoid the middle man involvement in rice purchasing process. PPC was related as the new concept of technology services that built in the area. Hence, the concept of theory of technology adoption would solve the issues that affect the use of PPC services among paddy farmers at Machang area. The Theory Acceptance Model (TAM) was used as the discipline of the study. The key determinant and factors were important in the study to determine the farmers’ perception towards PPC. The objectives of the study were used to identify the perception of farmers towards Paddy Purchasing Centre (PPC) in Machang, Kelantan. In order to achieve the objective, the specific objectives need to be determined. The specific objectives were to identify the respondents’ demographic profile, to examine the perception level of paddy farmers towards PPC in Machang, Kelantan and to clarify the relationship between socio demographic factor and the importance of PPC to paddy farmers. The information was obtained by using the questionnaire which consists of many questions that made to achieve the specific objectives. In descriptive analysis, the results showed that the farmers’ perception level towards PPC services were mostly in moderate levels. In chi square analysis, the demographic profiles such as the age, gender, marital status, education, agriculture education, total net income and the relationship between farmers and PPK Machang did related with farmers’ perception level towards PPC services. However, the most socio demographic profiles that were related to farmers’ perception level towards PPC services were age and the relationship between farmers and PPK Machang. Meanwhile, the logistic regression analysis showed that those demographic profiles did not show any significant different to farmers’ perception level towards PPC services. In conclusion, the farmers’ perception towards the PPC services in Machang, Kelantan did not be affected significantly by the socio demographic profiles among all of the paddy farmers, there. However, some demographic profiles might affect those perceptions in a different situation. Hence, a lot of recommendations need to be done in order to improve the study especially in terms of cooperation from respondents, variation of background profiles among respondents, the period of time of PPC services to be operated and also the right time to do the surveys among paddy farmers.